Production of Biogenic Nanoparticles for the Reduction of 4-Nitrophenol and Oxidative Laccase-Like Reactions - Capeness, Michael J.; Echavarri-Bravo, Virginia; Horsfall, Louise E. (Frontiers in Microbiology, 2019)
Biogenic nanoparticles present a wide range of possibilities for use in industrial applications, their production is greener, they can be manufactured using impure feedstocks, and often have different catalytic abilities compared to their chemically-made analogues. Nanoparticles of Ag, Pd, Pt and the bi-elemental PdPt were produced by Morganella psychrotolerans and Desulfovibrio alaskensis and were shown to be able to reduce 4-nitrophenol, an industrial and toxic pollutant. Nanoparticles were recovered post-reaction and then reused, thus demonstrating continued activity. Biogenic PdNPs were shown to have enhanced specificity in a wide pH activity range in the oxidation of the three common substrates ABTS, TMB and 2,6-DMP used to determine oxidase-like activity. Overall Pd in a nanoparticle form exhibited higher oxidation activity than its ionic counterpart, highlighting the potential of biogenic nanoparticles over the use of ions or chemically made elemental forms.